Current insights and future directions in systemic therapies for gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) in children and adolescents: a critical review of advancements and challenges - Michaela Kuhlen; Katharina Karges; Marina Kunstreich; Maximilian Schmutz; Antje Redlich; Rainer Claus; Constantin Lapa (EJC Paediatric Oncology)
Gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) in children and adolescents are rare and biologically heterogeneous. Due to their low incidence, therapeutic strategies are largely adapted from adult protocols, underscoring a critical need for paediatric-specific evidence.Surgical resection remains the mainstay of curative treatment for localized disease and should be prioritized before the initiation of systemic therapy whenever feasible. This review synthesizes current knowledge on systemic therapies in paediatric GEP-NENs,including somatostatin analogues (SSAs), peptide receptor radionuclide therapy (PRRT), chemotherapy, small molecules (e.g., everolimus, sunitinib), and immune checkpoint inhibitors (ICIs). While SSAs remain the mainstay for well-differentiated, somatostatin receptor (SSTR)-positive tumours, emerging data support the safety and potential efficacy of PRRT in paediatric populations, despite limited prospective evidence. Chemotherapy continues to play a role in high-grade or progressive disease, although responses are variable.Supportive therapies, including high-dose proton pump inhibitors (PPIs), are also important in managing functional tumours and can significantly alleviate clinical symptoms in advanced disease.Novel approaches, including SSTR antagonists, α- and β-emitting radiopharmaceuticals, and oncolytic virotherapy (e.g., SVV-001), are under active investigation in adults and may inform future paediatric protocols. Resistance mechanisms—particularly to SSAs—highlight the dynamic nature of tumour evolution and the need for individualized strategies.These insights underscore the importance of molecular profiling and imaging-based SSTR assessment to guide therapeutic selection, particularly in refractory or complex paediatric cases. Future efforts should prioritize international collaboration, the design of rational combination regimens, and the integration of radiomics, genomics, and biomarker-driven approaches to advance precision medicine in paediatric GEP-NENs.